Correctional Educators’ Perceptions of Juvenile Correctional Facilities Reflected in Metaphors (Training and Practice : Journal of Educational Sciences, 2022)
The juvenile detention center or reformatory is a specific world that operates simultaneously as a penal and a pedagogical institution. On the one hand, as part of the child protection system, it has an educational function, on the other hand, correctional education is a judicial measure applicable to juvenile offenders in the case of a criminal offense. The aim of the present study is to provide through correctional educators’ metaphors an insight into how educators relateto their workplace and the way they experience working in a closed institution. The metaphors used by correctional educators outline the specifics of the institution in a typical way; in addition, we can also obtain a large amount of information about the educational work carried out in the institution.